Sex Education for Elementary School Children in Indonesia; Bibliometric Analysis in 2021-2024 - Witasari, Rinesti (International Journal of Basic Educational Research, 2024)
This study provides an overview of the analysis of sex education trends in elementary school children in Indonesia for the 2021-2024 period using bibliometric analysis, aiming to identify research gaps that have not been widely studied and provide recommendations for further research. The method used is systematic literature review by utilizing Vosviewer as a meta-data analysis tool. Data was obtained from a POP search on Google Scholar 2021-2024 with the keyword "sex education for elementary school children", resulting in 107 articles that were then selected. The selection was carried out based on relevant themes, leaving 40 selected articles that fit the Sinta category and the highest ranking. The results of the study show that the trend of sex education research in elementary school age children has great potential to increase children's understanding of reproductive health and healthy social relations, and there is also an increase in research on this topic every year. This study recommends further research to develop an effective and applicable sex education learning model in learning activities in elementary schools.